Pendidikan Kesehatan Media Booklet Mengurangi Kecemasan Ibu pada Imunisasi Dasar di Era Pandemi Covid-19 - Mestika Lumbantoruan; Asima Sirait; Juneris Aritonang; Kristimone Andayani (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2022)
The Covid-19 pandemic has changed customary procedures, including causing disruptions in routine immunization programs. At the beginning of the Covid-19 pandemic in Indonesia, posyandu services had stopped and finally, during the implementation of immunization service activities, there was a decline. Data from observers of child immunization found that 83.9% of immunization services were disrupted due to the Covid-19 pandemic, the results in April 2020. One of factors was the feeling of worry and fear of mothers being infected with Covid-19 in health facilities including posyandu. Education is needed to change behavior of individuals for the better on this matter. This study aims to analyze health education with booklets on maternal anxiety in providing basic immunization in the era of the Covid-19 pandemic. The design of this study used quasi-experimental, data analysis using the Mc. Nemar. The results, there was an effect of providing health education with booklet media on the anxiety of mothers of babies 0-12 months in giving immunizations in the era of the covid-19 pandemic in the Desa Pekan Tanjung Morawa in 2021 with a p-value 0.015. There was a decrease in the number of respondents with mild anxiety from 65% to 33%, and no more respondents with moderate anxiety levels were found. The number of respondents who were not anxious increased by 39 people. The results of this study need to be carried out holistically related to immunization during the pandemic and others using booklets. Keywords: Health Education, Immunization, Maternal Anxiety, Media Booklets , The Covid-19 Pandemic